PILLOWED METABASALTS AND METABRECCIAS FROM THE VALAISAN OCEAN-CONTINENT TRANSITION PRESERVED IN THE BREUIL VALLEY, AOSTA (ITALIAN WESTERN ALPS) - Frasca, Gianluca; Compagnoni, Roberto (Ofioliti, 2021)
Subduction plate margins have an intrinsically poor preservation potential for pre-subduction settings because most rocks sink and disappear into Earth’s mantle. However, a preserved pre-subduction setting has been reported in the Lower Penninic Units (Valaisan Basin) of the Italian Western Alps (Beltrando et al., 2012). Here, we review two main aspects of the Valaisan Basin cropping out in Italy: the nature of the syn-rift detrital sediments and the characteristics of the metabasalts in proximity to the continental crust metagranitoid. New fossil findings are reported, which confirm a Mesozoic age for the Valaisan rifting. Field and petrographic data from metabreccias and pillowed metabasalts near the fossil-rich high-pressure metasediments support the interpretation of the Valaisan Domain in the Breuil valley (Aosta) as a fossil ocean-continent transition zone.